Determinan Minat dan Akseptabilitas Mahasiswa Terhadap Aktivitas Jual Beli Saham Online - Deni Wardani (Jurnal Keuangan dan Perbankan, 2018)
This study shows the relationship of several variables that can determine the effect on the intention to use in buying and selling shares online on the Indonesia Stock Exchange in an academic environment. This research focuses on online stock trading transactions among students on campus who have worked with securities institutions. This study uses the TAM and ECM models to develop the variables that become the material of analysis. Satisfaction, ease of use, Usefulness, trust, Risk and benefit variables are analyzed to see its relationship with intention to use using path analysis. The results of the discussion about this study show that the Satisfaction, Trust, Motivation and Investment Interest variables have a dominant influence on intention to use. Meanwhile, the Satisfaction and Ease of use variables influence trust, but Risk does not influence trust, and the Ease of Use variable with benefits does not have a positive effect on Usefulness. Satisfaction variable has an indirect effect on the intention to use through the trust variable, so does the Motivation variable has an indirect effect on the intention to use through the Investment Interest variable.